The Gold Leaves of Thailand’s Khao Chai Son and the Foluo’an Sea Route in Ling Wai Dai Da - Li, Daogang (Journal of Sinology (วารสารจีนวิทยา), 2016)
In 2014, gold ornaments including gold leaves from Song Dynasty were discovered in large quantity at Khao Chai Son District of Phatthalung Province in the South of Thailand. This article will prove and explain that the area is the ancient port called Suguna which is the destination in the Foluo’an sea route of Linyi people during the Song Dynasty. From this port people can sail towards the Western sea through the Malay Peninsula. The discovery of Suguna ancient port confirms that the Foluo’an sea route mentioned in Ling Wai Dai Da documents did exist.